Physical Preparation and Development of School Students (Journal of Pedagogical Inventions and Practices, 2021)
In this article, students will learn about different forms of organization of physical education, the important tasks of the physical education process, the features of physical health and development in relation to the child's age and opportunities at each stage of life, all body systems (musculoskeletal, cardiovascular, respiratory and others) and organs (control, hearing, sight, speech, etc.).